Hierarchical Organizations and Shared Responsibilities in the Low-Income Community of Dapeng in Shenzhen, China - LIU, Yiwei; JIA, Beisi (International Journal of Property Sciences (E-ISSN: 2229-8568), 2013)
Social housing for urban low-income communities is a major problem in Chinese urban housing. In China, standardization without rooms for participation in the current housing construction for low-income communities poses potential hazards to the social and living environments. The controversy over â€œuser participationâ€ in urban and architecture design originated at least 50 years ago when sharing rights and responsibilities were reconsidered. However, solutions that accommodate the need of inhabitants for more rights in making decisions on their own living space in social housing are still lacking. The concept of levels in the built environment was created by Habraken (1972), who aimed to provide a new design methodology that can identify the various responsible parties and their interaction with people, though such a concept can be observed in Chinese vernacular villages, which are often described as inherently flexible. Taking Dapeng as an example, a vernacular village in the suburban area of Shenzhen where the practice of participation of low-income people remains, this paper investigates various hierarchical organizations in the cultural context, village tissue and space hierarchy, building diversity and responsibility distribution of participants. Combined with the current living situation of low-income residents and the social housing dilemma, this paper suggests alternative approaches to achieve balance between professional responsibilities and user rights, and a new perspective on sustainable social housing in China.